On Presence: Spots of Time. - Runia, Eelco (History & Theory, 2006)
How can the subliminal, mysterious, but uncommonly powerful living-on, the presence, of the past be envisaged? In this essay I argue that presence is not brought about by stories—by, that is, the "storiness" of stories. Presence rather shows itself in how the past can force us—and enable us—to rewrite our stories about ourselves. The question then is how we acquire the experiences that can eventually force us to do so. How, and with what kind of things, does the mémoire involontaire—from which presence wells up—get filled? In order to answer this question one might turn it around to the question how we can fill the mémoire involontaire of others. A consideration of the "art of slandering" shows that the mémoire involontaire tends to get filled with things (1) that we believe are "common knowledge," that (2) are "obliquely" communicated, and that (3) are cast in metonymies. Metonymy offers a much better road to the mémoire involontaire than metaphor because metonymy is better at suggesting that what it conveys is "common knowledge." Therefore, I propose that presence resides in the metonymical region of language. Instead of being contained in the meaningful content (the "storiness") of stories, presence resides in what a story inadvertently has to be—in, that is, the things a story has to present in order to present a story. My conclusion is that as presence the past is the exact opposite of what historians think it is. It is indestructible, uncannily close, and—despite its closeness and its durability—utterly impossible to conserve in "representations" that can be taken along in the hand luggage with which we traverse time.